TeleSteer: Combining Discrete and Continuous Locomotion Techniques in Virtual Reality - Zhao, Ziyue; Li, Yue; Yu, Lingyun; Lianq, Hai-Ning (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Steering and teleporting are two common locomotion techniques in virtual reality (VR). Steering generates a great sense of spatial awareness and immersion but tends to lead to cybersickness; teleporting performs better in mitigating cybersickness but may lead to the loss of spatial awareness. Hence, we combined these two techniques and designed TeleSteer. This technique allows users to perform both steering and teleporting and customize the control. We discuss that a combined use of discrete (e.g. teleporting) and continuous (e.g. steering) locomotion techniques is necessary for scenarios that require both free explorations and close-range interaction tasks, making TeleSteer a suitable alternative.